Disclosing Medical Errors to Patients - Win May; Beverly Wood (MedEdPORTAL, 2010)
Abstract This is a standardized patient case that has been used to assess the communication skills of radiology residents when disclosing a medical error to a patient. In the case, a 50-year-old woman brings her young adult son for a CT scan. All goes well until shortly after the power injection of contrast media followed by saline. The son becomes apneic, hypotensive, and unresponsive, requiring resuscitation, for which the learner has called a code. The son is on his way to the intensive care unit after resuscitation and stabilization. The learner is unsure of the cause of the collapse, as the young man was in good health, an athlete, with no history to suggest a possible problem. The learner then meets with the patient's mother before she goes to the intensive care unit. The case content can be modified for use in other specialties, although the checklist for the standardized patient and the self-evaluation checklist for the resident can be used without modification by all residencies. The steps to be taken in disclosing an error to patients should be explicitly taught to residents by their respective programs. The standardized patient case materials have been extremely useful. The case was implemented in 2007 and used with two groups of radiology residents in two residency programs. Residents received it well and provided positive comments.